Features of the Onomasticon in Dramatic Poems by Lesja Ukrainka (Linguostylistic Studies, 2014)
The article deals with the literary onyms of dramatic poem by Lesja Ukrainka. Proper names testify about great purposeful work of the writer with the nominations of the personages: the chosen name conforms to the contextual usage and the plot, there are created variants and substitutions of the name which help the author to render his creative conception. Toponyms supply the text historical, ethnographic, connotative and other information, form the individual and author picture of the world.In the context of national spiritual values, which claims Lesya Ukrainka lips heroes, considered the most important for mankind themes of good and evil, honor and dishonor, love and hate, duty and self-denial. And so convincing to the reader sounded human postulates, the writer picked up interesting stories and striking heroic personality and their corresponding literary one, brim full of inherent in this lexical layer of artistic works of information and expression. Key words: proper name, onym, onomastic space, onomasticon, antrhoponyms,  toponyms. References